Role and Importance of Pulmonary Function test in Pulmonary Involvement of COVID-19: A Review Study - Kharazmi, Amir Behnam; Kashefizadeh, Alireza (Novelty in Biomedicine, 2024)
Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the greatest pandemic in the world. This virus involves the respiratory system, causes pulmonary dysfunction, and causes coronavirus disease (COVID-19). Pulmonary dysfunction due to COVID-19 may be asymptomatic, mild, moderate, and severe/critical. COVID-19 may involve other organs, and its sequelae may be persistent for a long time. The pulmonary function test is a method for evaluating the lungs in people. In this study, we reviewed the results of pulmonary function test (PFT) in patients with a history of COVID-19 involvement based on previous studies. Materials and Methods: The present review was conducted in 2024 using the keywords COVID-19, pulmonary function test, recovery, and pulmonary involvement in English. Eligible articles (articles containing the mentioned keywords) published during the years 2019 to 2023 were searched in Scopus, Pubmed, Wiley, and Google Scholar international databases. Relevant articles were identified, and after review, the most important and valuable points were presented. Results: PTF should not be done during COVID-19 involvement because it increases the rate of disease transmission. Small airway dysfunction, restrictive ventilatory dysfunction, and pulmonary diffusion impairment patterns are the most common findings in the PFTs of patients with a history of COVID-19. PFT improves gradually after the recovery of pulmonary involvement of COVID-19 for two years, even in patients with severe or critical forms of COVID-19. Conclusion: In this review, we summarized the results of studies about pulmonary function tests after COVID-19 involvement in survivors. Small airway dysfunction, restrictive ventilatory dysfunction, and pulmonary diffusion impairment are the most common findings in the PFT of survivors of COVID-19. These patterns are more prevalent among patients with severe or critical forms of COVID-19, and they are associated with the risk factors of COVID-19 severity, such as age, underlying disease, and pulmonary disorders. Forced vital capacity and diffusion capacity of lungs for carbon monoxide decreased in patients with COVID-19, and forced expiratory volume in 1 second (FEV1)/FVC and residual volume (RV) increased in these patients and they were associated with COVID-19 severity. The pulmonary involvement of COVID-19 recovers over time, and after two years, patients return to their baseline PFTs.